2008
DOI: 10.1080/13552070802120434
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of abortion in Nepal and menstrual regulation in Bangladesh: a gender analysis

Abstract: The extent to which abortion and menstrual regulation services are safe, legal, and women-friendly is a strong proxy of gender equity. This article draws on women's voices from Nepal and Bangladesh to illustrate that even where services are provided legally, women can still face multiple barriers to access to services, and problematic quality of care. This is exacerbated by the stigma which surrounds these services. Stigma is directly related to gender inequality, and is constructed at both the community and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…We focus on abortion care because it remains unclear what constitutes quality abortion care12 and because improving the quality of abortion care may lead to reductions in community-level abortion stigma13 and abortion-related morbidities and mortality 14–18. Improving abortion quality may also lead to increased post-abortion contraceptive knowledge18 and uptake 19…”
Section: Introductionmentioning
confidence: 99%
“…We focus on abortion care because it remains unclear what constitutes quality abortion care12 and because improving the quality of abortion care may lead to reductions in community-level abortion stigma13 and abortion-related morbidities and mortality 14–18. Improving abortion quality may also lead to increased post-abortion contraceptive knowledge18 and uptake 19…”
Section: Introductionmentioning
confidence: 99%
“…Some HCPs’ condescending attitudes toward Rohingya women and their tendency to view Rohingya women as a homogenous group with certain needs and desires could affect the quality of care provided. Research in a non-humanitarian setting in Bangladesh found that gendered norms and HCPs’ perceptions about clients affected the quality of care provided [ 23 ]. Making assumptions about clients’ needs and desires can take away their agency and reproductive decision-making capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, research into MR, PAC and FP has mainly focused on non-humanitarian settings [ 17 , 23 , 24 ]. The research has found that women and girls face barriers to accessing MR, PAC and FP services.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations